2014
DOI: 10.1186/1472-6750-14-31
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of enzyme blends to maximize the hydrolysis of alkaline peroxide pretreated alfalfa hay and barley straw by rumen enzymes and commercial cellulases

Abstract: BackgroundEfficient conversion of lignocellulosic biomass to fermentable sugars requires the synergistic action of multiple enzymes; consequently enzyme mixtures must be properly formulated for effective hydrolysis. The nature of an optimal enzyme blends depends on the type of pretreatment employed as well the characteristics of the substrate. In this study, statistical experimental design was used to develop mixtures of recombinant glycosyl hydrolases from thermophilic and anaerobic fungi that enhanced the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…Such blends can be further optimized by tailoring them for specific biomasses. Tailored blends might also decrease costs pertaining to enzyme production by utilizing an optimal ratio between the enzymes and thereby lowering the enzyme usage [8]. By improving the method of enzyme production a higher yield may be achieved, which would also increase the feasibility of biorefineries.…”
Section: Introductionmentioning
confidence: 97%
“…Such blends can be further optimized by tailoring them for specific biomasses. Tailored blends might also decrease costs pertaining to enzyme production by utilizing an optimal ratio between the enzymes and thereby lowering the enzyme usage [8]. By improving the method of enzyme production a higher yield may be achieved, which would also increase the feasibility of biorefineries.…”
Section: Introductionmentioning
confidence: 97%
“…According to Khattak et al ., the utilization of sugars from feed during microbial conversion of cellulose is a crucial drawback. Also, feedback inhibition of cellulases by both intermediate and end products has been widely reported . Nevertheless, it should be observed that Tween 20 was able to maintain the performance and functionality (stability) of the cellulases better than CaCl 2 during EFB saccharification.…”
Section: Resultsmentioning
confidence: 98%
“…Cel7B might improve overall cell wall conversion through the hydrolysis of polysaccharides covering the cellulose microfibers and thus making them exposed to cellulase action. In addition, Cel7B are capable of generating more reducing and non-reducing ends, available to Cel7A and Cel7B attack (Badhan et al 2014). Based on ThCel7B biochemical characterization, we speculate that this enzyme might be equally important for biomass enzymatic hydrolysis, not only directly synergizing with exoglucanases in cellulose microfibers depolymerization but also making them available for cellobiohydrolase action through active hydrolysis of other polysaccharides of the plant cell wall matrix.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that enzymatic hydrolysis of alkaline peroxide pretreated alfalfa hay and barley straw by rumen enzymes and commercial cellulases was significantly enhanced by addition of endoglucanase from GH7 family (Badhan et al 2014). Augmented glucose release as a consequence of the endoglucanase addition was thought to be the result of its broad substrate specificity (Badhan et al 2014). Cel7B might improve overall cell wall conversion through the hydrolysis of polysaccharides covering the cellulose microfibers and thus making them exposed to cellulase action.…”
Section: Discussionmentioning
confidence: 98%